1998
DOI: 10.1038/31242
|View full text |Cite
|
Sign up to set email alerts
|

Gli/Zic factors pattern the neural plate by defining domains of cell differentiation

Abstract: Three cell types differentiate in the early frog neural plate: neural crest at the lateral edges, floorplate at the midline and primary neurons in three bilateral stripes. Floorplate cells and ventral neurons are induced by Sonic hedgehog (Shh) and neural crest and dorsal neurons are induced by epidermal factors such as bone morphogenetic proteins (BMPs). Neurogenesis in a subset of cells within the stripes involves lateral inhibition. However, the process by which pools of precursors are defined in stereotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
206
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(220 citation statements)
references
References 23 publications
10
206
0
1
Order By: Relevance
“…5A). Of the three family members, Gli2 had the strongest neurogenic properties (42,43). It has recently been shown that Gli2 induces neuronogenesis but not gliogenesis in neuronal stem cells by positively regulating the expression of some neurogenic basic helix-loop-helix genes such as Mash1 (43).…”
Section: Shh Pathway Activation In Neuronal Precursor Cell Cultures Fmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). Of the three family members, Gli2 had the strongest neurogenic properties (42,43). It has recently been shown that Gli2 induces neuronogenesis but not gliogenesis in neuronal stem cells by positively regulating the expression of some neurogenic basic helix-loop-helix genes such as Mash1 (43).…”
Section: Shh Pathway Activation In Neuronal Precursor Cell Cultures Fmentioning
confidence: 99%
“…Gli proteins (Gli1, Gli2, and Gli3) were recently shown to be involved during neurogenesis in vivo, creating a dynamic physical network (41). Of the three family members, Gli2 had the strongest neurogenic properties (42,52). In particular, it has been shown that overexpression of Gli2 induces neuronogenesis, but not gliogenesis in P19 EC cells, and increases the expression of the pro-neurogenic gene Mash1 (43).…”
Section: The App/aicd-dependent Alteration Of the Shh Pathway Impairsmentioning
confidence: 99%
“…In this paper, we showed the impaired differentiation of dorsal neural plate (neurulation delay) in Zic2 kd/kd embryo, which is concomitant with the expression lag of Wnt3a. This finding is consistent with the result from a gain of function experiment using Xenopus embryo, from which Brewster et al (19) proposed that Xenopus Zic2 is a prepattern gene required for the differentiation of dorsal neural tube including its derivative. As determined by the BrdUrd assay, the cell proliferation was not significantly decreased in the dorsal neural tube of the Zic2 mutant (data not shown) whereas the reduction of cerebellar granule cell proliferation was indicated in the Zic1 mutant (7).…”
Section: Discussionsupporting
confidence: 82%
“…We ®nd that overexpression of Xmeis1 in ectodermal explants induces XGli-3 and XZic3 expression, while XGli-1 is not a ected (Figure 4). Gli and Zic genes, like Xmeis1b, induce neural tissue in animal cap explants (Nakata et al, 1997;Ruizi Altaba, 1998;Brewster et al, 1998;Matise et al, 1998;Ding et al, 1998) and it is interesting that Xmeis1b induces XGli-3 which is normally expressed in dorsal neural tube from where neural crest emanates (Marine et al, 1997), but does not induce XGli-1 which is found ventrally within the neural tube. Moreover, transverse sections revealed that Xmeis1b induced an accumulation of ectopic pigmented cells in the embryo, and pigmented cells are often derived from neural crest.…”
Section: Discussionmentioning
confidence: 99%
“…Zic3, a member of the Gli gene superfamily (Brewster et al, 1998), is a prepattern gene that also induces pigmented cell masses in Xenopus embryos and promotes the earliest steps in neural and neural crest development (Nakata et al, 1997). Therefore, it was of interest to determine whether the Xmeis1 protooncogene could activate the Gli/Zic pathway.…”
Section: Expression Pattern Of Xmeis1 Suggests a Role In Neural Crestmentioning
confidence: 99%